Anti-hepatocellular carcinoma activity of Jacaranda mimosifolia through experimental validation and network pharmacology - Ayesha Bibi; Muhammad Hamza Afandi; Azra Mehmood; Usman Ali Ashfaq; Muhammad Shareef Masoud; Mohsin Ahmad Khan; Rashid Bhatti (PLoS ONE, 2026)
Hepatocellular carcinoma (HCC) has a very significant mortality rate and is one of the most common cancers worldwide. Jacaranda mimosifolia is reported to have potential antitumor activities against various human cancers. However, the effects of J. mimosifolia on HCC are yet elusive. This study aimed to investigate the anti-HCC potential of methanolic extract of J. mimosifolia leaves using in vitro and in vivo studies and a network pharmacology approach. The effect of J. mimosifolia extract was assessed on Huh-7.5 cells using MTT assay, wound healing assay, and DNA fragmentation assay. These experiments found that J. mimosifolia extract significantly suppressed Huh-7.5 cell proliferation, impaired cell migration, and induced cell apoptosis. The real-time PCR validated the upregulation of p53 and Bax , alongside the downregulation of AFP and GPC3 in Huh-7.5 cells after treatment with J. mimosifolia extract. In vivo experiments confirmed the hepatoprotective effects of J. mimosifolia extract in mice models with CCl 4 -induced hepatic injury. In addition, through network pharmacological analysis, J. mimosifolia was found to play a critical role against HCC via targeting multiple potential targets and pathways. Docking analysis identified apigenin and kaempferol with the lowest binding energy against PTGS2 and EGFR, respectively, while flavonol glycoside showed the lowest binding energy against MMP9. However, detailed research is needed to isolate the potential phytochemicals from J. mimosifolia against HCC.